2017
DOI: 10.7554/elife.23172
|View full text |Cite
|
Sign up to set email alerts
|

Ambra1 spatially regulates Src activity and Src/FAK-mediated cancer cell invasion via trafficking networks

Abstract: Here, using mouse squamous cell carcinoma cells, we report a completely new function for the autophagy protein Ambra1 as the first described ‘spatial rheostat’ controlling the Src/FAK pathway. Ambra1 regulates the targeting of active phospho-Src away from focal adhesions into autophagic structures that cancer cells use to survive adhesion stress. Ambra1 binds to both FAK and Src in cancer cells. When FAK is present, Ambra1 is recruited to focal adhesions, promoting FAK-regulated cancer cell direction-sensing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…The trafficking of Src between focal adhesions and the cell interior, which is regulated by activating molecule in Beclin1-regulated autophagy (Ambra1) and focal adhesion kinase (FAK), is important for cell migration and metastasis. Ambra1 redirects Src towards autophagosomes to disfavor substrate attachment and favor cell movement in an IFITM3-dependent manner [ 78 ] (Fig. 2 ).…”
Section: Moonlighting In the Membranesmentioning
confidence: 99%
“…The trafficking of Src between focal adhesions and the cell interior, which is regulated by activating molecule in Beclin1-regulated autophagy (Ambra1) and focal adhesion kinase (FAK), is important for cell migration and metastasis. Ambra1 redirects Src towards autophagosomes to disfavor substrate attachment and favor cell movement in an IFITM3-dependent manner [ 78 ] (Fig. 2 ).…”
Section: Moonlighting In the Membranesmentioning
confidence: 99%
“…The second pathway is engaged to maintain cell viability when the FAK/Src pathway is severely compromised and involves c-Cbl-mediated autophagic targeting of Src [ 141 ]. The targeting of Src to autophagosomes is controlled by the autophagy regulator Ambra1 (Activating Molecule in Beclin1-Regulated Autophagy) and requires Ambra-binding proteins such as Dynactin 1 and IFITM3 (Interferon-Induced Transmembrane protein 3) [ 142 ]. Nevertheless, in the presence of FAK, Ambra bind to the FAK PR3 domain thereby controlling the spatial regulation of FAK/Src at FAs.…”
Section: Fak Structural Determinant For the Search Of Potent Fak Imentioning
confidence: 99%
“…Various studies have demonstrated a key role for autophagy in focal adhesion dynamics during cell migration and invasion . Inhibition of focal adhesion kinase (FAK), such as occurs during cell detachment from the substratum, resulted in autophagic degradation of active SRC kinase.…”
Section: Autophagic Control Of Tumor Cell Migration and Invasionmentioning
confidence: 96%
“…This required c‐CBL, a SRC‐binding protein, and E3 ubiquitin ligase that contains a LIR motif and interacts directly with processed LC3B to promote autophagic turnover of SRC . SRC turnover by autophagy also required Ambra1, a multifunctional protein known as an inhibitor of the Beclin1‐VPS34 initiation complex but that alternatively can interact with FAK to limit active SRC at focal adhesions and promote SRC degradation by autophagy . Inhibition of autophagy restored SRC expression at focal adhesions in adhesion‐stressed cells but was associated with cell death indicating that autophagic turnover of SRC was required in response to cell detachment or FAK inactivation (Fig.…”
Section: Autophagic Control Of Tumor Cell Migration and Invasionmentioning
confidence: 99%